2013
DOI: 10.1017/s1368980013001365
|View full text |Cite
|
Sign up to set email alerts
|

Eating for the better: a social marketing review (2000–2012)

Abstract: Objective: The present study sought to identify both the ingredients for success and the potential impediments to social marketing effectiveness for healthy eating behaviour, focusing on studies conducted over the last 10 years. Design: A comprehensive literature review was undertaken examining seventeen databases to identify studies reporting the use of social marketing to address healthy eating. Thirty-four empirical studies were analysed to examine the effectiveness of social marketing interventions to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
265
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(292 citation statements)
references
References 75 publications
16
265
0
11
Order By: Relevance
“…The nutritional social marketing initiatives review by Carins and Rundle-Thiele (2013) revealed that adults are a neglected target group for nutritional interventions. In particular, young adults are prone to unhealthy eating behaviour (Kafatos et al 2000;Fotiadou and Hassapidou 2001;Papadaki et al 2007) especially after embarking on third level education when they begin to live away from their families (Beasley et al 2004;Sharma et al 2009;Riddell et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The nutritional social marketing initiatives review by Carins and Rundle-Thiele (2013) revealed that adults are a neglected target group for nutritional interventions. In particular, young adults are prone to unhealthy eating behaviour (Kafatos et al 2000;Fotiadou and Hassapidou 2001;Papadaki et al 2007) especially after embarking on third level education when they begin to live away from their families (Beasley et al 2004;Sharma et al 2009;Riddell et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…While some programmes cast a wide net to form a coalition of diverse individuals and organisations that are community stakeholders, others target a subset of midstream actors such as family and peer groups (Carins and Rundle-Thiele, 2014). There is also variety in roles played by different actors (Dibb, 2014;Whitelaw et al, 2010), for instance community members may be involved in problem diagnosis and intervention design and public service professionals or trained researchers take responsibility for evaluation.…”
Section: Midstream Social Marketingmentioning
confidence: 99%
“…Existing literature provides some insight into the factors that motivate and inhibit collaboration amongst community actors, but systematic analysis to address question of why and how they work -their dynamics and conditions conducive to success -is sorely needed (Carins and Rundle-Thiele, 2014;Truong, 2014;Whitelaw et al, 2010).…”
Section: Midstream Social Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass media social marketing campaigns analysed, reported and founded in 2014) are deemed to have evidence of each of Andreasen's (2002) six social marketing benchmarking criteria (Carins & Rundle-Thiele, 2013 …”
Section: Mass Media Social Marketingmentioning
confidence: 99%